2022
DOI: 10.7554/elife.84171
|View full text |Cite
|
Sign up to set email alerts
|

R-spondin 3 deletion induces Erk phosphorylation to enhance Wnt signaling and promote bone formation in the appendicular skeleton

Abstract: Activation of Wnt signaling leads to high bone density. The R-spondin family of four secreted glycoproteins (Rspo1-4) amplifies Wnt signaling. In humans, RSPO3 variants are strongly associated with bone density. Here we investigated the role of Rspo3 in skeletal homeostasis in mice. Using a comprehensive set of mouse genetic and mechanistic studies, we show that in the appendicular skeleton, Rspo3 haplo-insufficiency and Rspo3 targeted deletion in Runx2+ osteoprogenitors lead to an increase in trabecular bone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…S3, C and D). These data suggest that the role of TGR5 on bone microarchitecture differs based on skeletal location, which is in line with the recently described differential regulation of the axial and the appendicular skeleton 43,44 .…”
Section: Resultssupporting
confidence: 90%
“…S3, C and D). These data suggest that the role of TGR5 on bone microarchitecture differs based on skeletal location, which is in line with the recently described differential regulation of the axial and the appendicular skeleton 43,44 .…”
Section: Resultssupporting
confidence: 90%
“…These observations suggest that the effect of adipogenic Dkk1 deletion on bone mass may be age dependent. Previous studies have shown that the role of Dkk1 in bone remodeling is complex and varies depending on the stage of skeletal development and the type of bone being examined ( 44 , 45 , 46 , 47 , 48 ). In addition, it is well-known that adipogenesis increases with aging and is linked with reduced bone formation ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…65 ERK phosphorylation is pivotal to osteoblast differentiation and the balance between bone formation and resorption. 66 Bandow et al showed on osteoblasts angiotensin type 1 (AT1) inhibitors could counteract LIPUS-induced ERK phosphorylation and RANKL expression. 67 However, it is unclear whether the AT1 inhibitor can reverse the LIPUS-induced upregulation of COX-2 and PEG2.…”
Section: Mechanism Of Lipus On Fracture Healingmentioning
confidence: 99%
“…Koukubu et al found LIPUS treatment in mouse osteoblasts upregulated COX‐2 mRNA expression and consequently higher PGE2 production 55 through presumably the integrin/FAK/PI3K/Akt and ERK signaling pathways 65 . ERK phosphorylation is pivotal to osteoblast differentiation and the balance between bone formation and resorption 66 . Bandow et al showed on osteoblasts angiotensin type 1 (AT1) inhibitors could counteract LIPUS‐induced ERK phosphorylation and RANKL expression 67 .…”
Section: Mechanism Of Lipus On Fracture Healingmentioning
confidence: 99%